Integral Sliding Mode and Integral Supertwisting Sliding Mode Control for Ship Course-Keeping - Muhammad Munir Butt; Azhar Iqbal Kashif Butt; Iftikhar Ahmad (IEEE Access)
This paper proposes variable structure-based nonlinear control algorithms, including synergetic, terminal synergetic, integral sliding mode, and integral supertwisting sliding mode controllers, for ship course-keeping. The global asymptotic stability of the system is ensured using Lyapunov stability theory. Simulations are conducted using the Simulink toolbox in the MATLAB environment. The smoothness, energy consumption, and output response performances of the proposed controllers are evaluated to verify their effectiveness. Finally, a comparative analysis is presented to demonstrate the efficiency of the proposed controllers relative to each other and to existing controllers from the literature for ship course-keeping control.